Epidemiologia do HIV/AIDS em população adulta do Chile, no período de 2000 a 2017 - Sanzana, Carlos Erasmo Sanhueza (2020)
Introduction: HIV/Aids infection is an epidemic of importance to global public health, that has claimed millions of lives. It is estimated that 38 million People lives with HIV/Aids (PLWHA) in the world, TB-HIV coinfection it remains the to be the main cause of death in PLWHA, especially in developing countries. Objetive: Describe the epidemiological and clinical characteristics of HIV/Aids infection in the adult Chilean population between 2000 to 2017 period. Method: This is an a multi-method retrospective observational study; analyzing the prevalence of new HIV/Aids infections in the adult population over 15 years of age, based on the Records of Compulsory Notification Disease (ENO) of 26,143 reported cases. It was applied Fisher's exact and Pearson´s chi-square test for variables associated with the prevalence of HIV/Aids. In addition, a survival study of 17,512 people admitted to antiretroviral therapy in the public health system was carried out. Non-parametric Kaplan Meier and Cox regression models were performed for associated variables with mortality from TB-HIV coinfection. Results: It was observed an increase of new HIV/Aids infections in young population (15 to 29 years old). We found an increase of the prevalence of HIV in men who have sex with men (MSM) population, and a reduction in the male-female ratio from 7.2 to 5.2. We found an increase of 200% of new HIV infections of indigenous peoples, between Aymara and Mapuche ethnic groups. The regions with the highest prevalence rates were founded in Arica and Parinacota with 22.4/100,000 hab. Valparaíso 6.7 and Metropolitana 6.9. It was observed that 11% of people died, incidence density 0.05 per 39,283 person-years. The following variables characterized a risk factor for death: TB-HIV coinfection (HR 1.4; CI95%: 1.2-1.7), CD4+ liphocytes<500 cel/mm³ (HR 3.2; CI95%: 2.2-4.9), a load viral of admission to treatment >10,000cop/uL (HR 1.3; CI95%: 1.2-3.0). Secondary school or higher education was a protective factor for deaths from TB-HIV coinfection (HR 0.76; CI95%: 0,6-0.9). Conclusion: The HIV/Aids epidemic in Chile is experiencing a scenario of feminization of HIV, the mortality was concentrated in TB-HIV coinfected people. Additionally, indigenous peoples, such as the Aymara and Mapuche emerge as vulnerable populations to the epidemic. We suggest improvements in combined prevention, access to community-based strategies, sex education in schools and structural interventions in the field of public policy issues.